2014
DOI: 10.7860/jcdr/2014/8359.4597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Periodontal Health

Abstract: Aims and Objectives: The aim of the study was to assess and compare the effect of smoking on mRNA expression of MMP -8 and TIMP-1 in patients with untreated chronic periodontitis and in periodontally healthy subjects and to examine the correlation of MMP-8 and TIMP-1 levels with clinical parameters. Materials and Methods:Out of 60 subjects, 40 were selected subjects for the study, and were divided into Group I (periodontitis subject) and Group II (healthy subjects). Each group was further subdivided into subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Smoking is a potential risk factor for various systemic diseases including periodontal disease. 15 , 16 Previous studies 16 , 17 demonstrated a significant biological plausibility on the relationship of smoking and periodontal disease. However, there is a gap in relation to dose response of smoking and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a potential risk factor for various systemic diseases including periodontal disease. 15 , 16 Previous studies 16 , 17 demonstrated a significant biological plausibility on the relationship of smoking and periodontal disease. However, there is a gap in relation to dose response of smoking and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%